Interactive-Based Learning Media Design To Achieve Students' Learning Outcomes In The Subject Of Islamic Cultural History In Class X Mas Ushuluddin - Rubi Awalia; Syahruddin Usman; Abdul Rahman Sakka; Aslan (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Islamic Cultural History Learning plays an significant part in forming pupils' Islamic understanding and character. Conventional learning approaches, however, frequently get in the way of attaining the best possible learning results. In order to increase learning effectiveness and learning outcomes, this project attempts to create interactive learning materials of students in class X of Ushuluddin Private Madrasah Aliyah (MAS). This study uses a descriptive method based on facts in the field. Data collection techniques in a study are very important, in order to obtain data that is in accordance with the focus to be studied. Because the research data is qualitative research, the researcher chose a data collection technique using in-depth interviews, observation, and documentation. The results of the study showed that the use of interactive-based learning media made students more actively involved in the learning process, which ultimately strengthened their conceptual understanding and improved academic achievement in studying Islamic Cultural History. The construction of interactive multimedia-based learning materials to enhance students' learning outcomes in Islamic Cultural History classes is the study's conclusion X MAS Ushuluddin integrating with text, images, audio, video, and other interactive elements, this media not only succeeded in creating a more interesting and motivational learning environment but also facilitated students' deep understanding of the material.